Effects of ocean acidification on phenology and epiphytes of the seagrass Posidonia oceanica at two CO vent systems of Ischia (Italy) Abstract - Mecca, Silvia; Casoli, Edoardo; Ardizzone, Giandomenico; Gambi, Maria Cristina (Zenodo, 2020)
Mecca, Silvia, Casoli, Edoardo, Ardizzone, Giandomenico, Gambi, Maria Cristina (2020): Effects of ocean acidification on phenology and epiphytes of the seagrass Posidonia oceanica at two CO vent systems of Ischia (Italy) Abstract. Mediterranean Marine Science 21 (1): 70-83, DOI:10.12681/mms.20795, URL: http://dx.doi.org/10.12681/mms.20795